2021
DOI: 10.1021/acs.jpca.1c07623
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Combustion Kinetics of OH Radical Reactions with a C5 Unsaturated Alcohol: The Competitive H-Abstraction and OH-Addition Reactions of 2-Methyl-3-buten-2-ol

Abstract: 2-Methyl-3-buten-2-ol (MBO232) is a potential biofuel and renewable fuel additive. In a combustion environment, the consumption of MBO232 is mainly through the reaction with a OH radical, one of the most important oxidants. Here, we predict the intricate reactions of MBO232 and OH radicals under a broad range of combustion conditions, that is, 230–2500 K and 0.01–1000 atm. The potential energy surfaces of H-abstraction and OH-addition have been investigated at the CCSD­(T)/CBS//M06-2X/def2-TZVP level, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It is believed that the accuracy of energetic calculations using double-hybrid functionals with dispersion corrections can approach the accuracy of wave function methods while requiring computational efforts comparable to those of hybrid functionals (with the RI speedup technique) . However, according to our comprehensive survey of the literature on the choices at the theory level for describing H-abstraction reactions since 2015, ,,, it has been concluded that only a few studies have been conducted on the performance of double-hybrid functionals in the description of H-abstraction reactions. Subsequently, rev-DSD-PEBP86-D3­(BJ), wB97X-2-D3­(BJ), and PWPB95-D3­(BJ) were tested to calculate the electronic energies of the acquired molecular structures.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…It is believed that the accuracy of energetic calculations using double-hybrid functionals with dispersion corrections can approach the accuracy of wave function methods while requiring computational efforts comparable to those of hybrid functionals (with the RI speedup technique) . However, according to our comprehensive survey of the literature on the choices at the theory level for describing H-abstraction reactions since 2015, ,,, it has been concluded that only a few studies have been conducted on the performance of double-hybrid functionals in the description of H-abstraction reactions. Subsequently, rev-DSD-PEBP86-D3­(BJ), wB97X-2-D3­(BJ), and PWPB95-D3­(BJ) were tested to calculate the electronic energies of the acquired molecular structures.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…However, the hydrogen bond can also decrease the rate constant due to the entropy losses. 62,63 To uncover the hydrogen-bonding effect and the contributions of different conformers on the thermodynamic quantities, the results for SP2a are presented in Fig. 4 as an example.…”
Section: Hydrogen Bonding Analysis and Thermodynamic Quantitiesmentioning
confidence: 99%